Rancang Bangun Power Supply Adjustable Untuk Sepeda Motor Dan Mobil: Rancang Bangun Power Supply Adjustable Untuk Sepeda Motor Dan Mobil - Prasetyoaji, Yuka Dimas (Jurnal Rekayasa Mesin, 2020)
The use of batteries when repairing a car or motorcycle is at risk of being damaged because the stater motor is used repeatedly to get fuel and air input in the combustion chamber, therefore we need a tool that serves to replace the battery during the service process and can reduce waste. This study aims to provide convenience in the trainer trial process and accelerate the learning process of car and motorcycle trainer practice using Adjustable Power Supply. The methodology of making an Adjustable Power Supply tool uses the design method. The use of Adjustable Power Supply tool on car and motorcycle trainers obtained the values of Volt, Ampere, Watt as follows 10,3 Volts, 105 Ampere, and 680 Watts for 5k Kijang trainers, and 9,5 Volt, 8,8 Ampere and 87 Watts for Supra X 125 motorcycle trainers, on average, are stable. The use of a Adjustable Power Supply replacement tool is stable and can be used efficiently. The adjustable power supply is more efficient compared to using the battery at the Gasoline Motor Laboratory because it does not need to recharge the battery so the practicum is more optimal. This tool can solve the problem of wasteful use of batteries in the gasoline motor laboratory Keywords: adjustable power supply ;batteries ;design method.